PERMAINAN ABC 5 DASAR DALAM MATA PELAJARAN BAHASA JAWA MATERI AKSARA JAWA HANACARAKAN PADA KELAS RENDAH - Diah Ayu Pamukir AY; Arissona Dia Indah Sari (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This research aims to determine the Javanese hanacaraka script in the traditional ABC 5 basic game in Javanese language learning for grade 1 MI students. The research method used is a qualitative approach with data collection techniques through observation and interviews, through the use of the Javanese hanacaraka script. Students are exposed to learning experiences that include cultural aspects and traditional values ​​in the context of the Javanese language. The results of the research show that the use of the Javanese hanacaraka script in the basic ABC 5 game is very effective in improving students' memorization understanding. Students are actively involved in this game, practicing their memory skills by naming the Javanese script. By doing this, they not only develop Javanese language skills but also gain a deeper understanding of the culture.